Desempenho da soja cultivada em solo hidromórfico e não hidromórfico com e sem irrigação suplementar - Rocha, Thiago Schmitz Marques da (2016)
Soybean (Glycine max (L.) Merrill) is the major legume crop in the world. Rio Grande do Sul State is an important national grain producer, and the area grown with soybean has been expanded to areas of lowlands traditionally used to grow rice. In lowland areas the deficit and water surplus is more common due to physical properties of the soil. The objective of this dissertation is to characterize growth and development, and to quantify gas exchange at the leaf level and grain yield of two soybean cultivars with indeterminate and determinate stem termination in a hydromorphic soil and in a non-hydromorphic, with and without irrigation. Field experiments were conducted during the 2014/2015 growing season in Santa Maria, RS and Cachoeirinha, RS with two soybean cultivars, with determinate (Nidera NA 6411 RG) and indeterminate (TECIRGA 6070 RR) stem termination. In Santa Maria, the experiment was conducted with and without irrigation. Irrigation was performed by dripping and based on soil water balance. In Cachoeirinha, the experiment was conducted in a paddy field for rice cultivation, and irrigation was performed by flooding according to the water tension in the soil and stage of development of culture. Evaluations of development growth, yield components, gas exchange and dry matter were performed. The available water capacity for the crop in rotation with rice is limited mainly by the compacted layer of the soil near the surface. The main feature that ensures the highest yield stability of cultivars with indeterminate stem termination is the longest duration of the flowering period. Small water stress, either by deficit or surplus, that often take place in hydromorphic soil grown with soybean did not affect dry matter partitioning but did affect gas exchange and leaf area, which in turn did not affect grain yield. Defense mechanisms to water stress were activated, such as reduced stomatal conductance, photosynthetic rate and leaf area.